THE EFFECT OF ROUND TABLE TECHNIQUE ON THE WRITING ABILITY IN RECOUNT TEXT OF THE SECOND YEAR STUDENTS OF SMPN 1 KUBU - Fitri, Auliana; Azhar, Fadly; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research is to find out whether there is an effect of Round Table Technique on the students’ writing ability in recount text of SMPN 1 Kubu. This research was applied by using one-group-pretest-posttest design. In conducting this research, a single group was selected to be a sample by using Cluster Random Sampling. There are 33 students as the sample. In order to know the difference between the pre-test and the post-test and to analyse the hypothesis, t-test formula was used. After analysing the data, the writer found that t-obs score was 11.738 while the value of t-table is 2.037. Since t-obs (11.738) was higher than t-table (2.037), it can be concluded that null hypothesis was rejected. It means that there is a significant effect of Round Table Technique on the students’ writing ability at SMPN 1 Kubu in writing recount text. Based on the research findings, it is recommended that teachers use Round Table Technique to help the students to generate their ideas in writing a recount text.Key Words: Effect, Round Table Technique, Writing Ability, Recount Text